Pemberdayaan Ibu Rumah Tangga Melalui Usaha Kue Basah Tradisional untuk Meningkatkan Pendapatan Keluarga - Sri Budi Cantika Yuli; Bambang Widadgo; Zainal Arifin (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2025)
There are two main problems in the Housewives group in Bocek Village, Karangploso District, Malang Regency. They are how to develop an entrepreneurial spirit, so that this Housewives group can use their time by opening business opportunities that generate additional household finances and technology improvement through the assistance of cooking utensils, stoves, packaging plastics, to obtain efficiency and effectiveness from the production process. The solution offered to overcome the problems is training and mentoring on making various traditional wet cake products such as Chocolate Banana (Piscok), Pastel, and Mayonnaise Risoles with good taste variations in the scope of processing, packaging, and marketing so that they can be attractive and appeal to new customers/consumers, especially being able to follow the tastes of the community/consumers. The method of activities that will be carried out by the PIM Team is training and mentoring for partners. Training and mentoring include: increasing knowledge about entrepreneurship, fostering entrepreneurial spirit for Housewives groups, and pioneering household businesses in making wet cakes such as Chocolate Banana (Piscok), Pastel, and Mayonnaise Risoles.